Use and knowledge of contraceptive methods by patients in two substance use disorders treatment centers in Paris - Virgile Clergue-Duval; Suzanne Robin; Maeva Fortias; Gaël Dupuy; Béatrice Badin-; Florence Vorspan (BMC, 2017)
Abstract Background Studies on contraceptive use by patients with substance use disorders (SUD) show a concerning low use of contraception. Mainly conducted in USA, they could be irrelevant to patients attending European SUD treatment centers, especially since these studies mostly investigate women suffering from social exclusion, severe material deprivation andopiates use with frequent high-risk drug use and sexual behaviors including sex trade, frequently not currently attending treatment centers. The purpose of this study is to describe contraceptive use by patients, both male and female, since contraception can not only be considered as a female problem, with severe SUD in two free clinics in Paris, France. Methods An anonymous self-report questionnaire was distributed to literate patients followed in two generalist substance use disorders treatment centers in hospitals of Paris, France: Espace Murger and Centre Cassini, during 5 weeks between February and March 2016. Results Out of the 78 respondents (with an age mean 40.7 years, in which women are represented as 48.1%, and 29.7% of them have children), 53 have had at least one sexual partner in the last 6 months. Contraception was "always" used by 55.3% of sexually active patients, "sometimes" by 19.1%, and "not" used by 25.5%. Male condoms were the main contraceptive method. The use of intrauterine devices was low, contrarily to what is observed in the French general population. However, the knowledge of contraceptive methods was common. Conclusions In this population, with a high prevalence of at risk sexual behavior, the use of contraceptive methods is lower than in French general population. During standard care for SUD, contraception and desire to be a parent should be discussed and patients empowered to make their own choices. Lack of knowledge does not seem to be a hindrance to the use of contraception, but other sociological, psychological, or medical factors may limit contraceptive access and long-term use, especially for the long-acting reversible contraception methods. It is necessary to further develop this reflection by discussing the individual contraceptive choices with the patients themselves to clarify the nature of these constraints and maybe provide several contraceptive methods within the SUD care settings.